1987
DOI: 10.1037/0022-3514.52.5.881
|View full text |Cite
|
Sign up to set email alerts
|

The cognitive–affective crossfire: When self-consistency confronts self-enhancement.

Abstract: Self-consistency theory assumes that people want others to treat them in a predictable manner. Selfenhancement theory contends that people want others to treat them in a positive manner. We attempted to help reconcile the two theories by testing the hypothesis that people's cognitive responses conform to self-consistency theory and their affeetive responses conform to self-enhancement theory. We presented individuals who possessed either positive or negative self-concepts with either favorable or unfavorable s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
414
3
6

Year Published

1988
1988
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 513 publications
(453 citation statements)
references
References 28 publications
30
414
3
6
Order By: Relevance
“…At first glance, it may seem odd that we did not observe a similar interaction for the manipulation check measure tapping participants' feelings of pleasantness and satisfaction. However, this observation is in full agreement with other work on self-perception that suggests that affective reactions to feedback about (non-)possession of desired characteristics are not moderated by self-definition, whereas perceptual or cognitive reactions are (Swann, Griffin, Predmore, & Gaines, 1987).…”
Section: Manipulation Checkssupporting
confidence: 90%
“…At first glance, it may seem odd that we did not observe a similar interaction for the manipulation check measure tapping participants' feelings of pleasantness and satisfaction. However, this observation is in full agreement with other work on self-perception that suggests that affective reactions to feedback about (non-)possession of desired characteristics are not moderated by self-definition, whereas perceptual or cognitive reactions are (Swann, Griffin, Predmore, & Gaines, 1987).…”
Section: Manipulation Checkssupporting
confidence: 90%
“…On the basis of a drive-reduction model, these theorists have proposed that people with low self-esteem seek self-aggrandizement more avidly than do those with high self-esteem, and that self-enhancement biases are therefore more prevalent among those with low self-esteem than those with high self-esteem. Self-consistency theorists, however, have emphasized the degree to which individuals actively strive to preserve their current self-conceptions (Lecky, 1945;Swann, 1987). According to this model, people with high self-estcem seek to confirm their positive self-views and those with low selfesteem, their negative self-views.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, both [17] and [18] found that, whereas cheerful people regarded flattering feedback as more accurate than critical feedback, depressed people regarded critical feedback as more accurate than positive feedback. They also found that, whereas feedback desirability did not predict feedback or interaction partner choice, perceived feedback accuracy did (see also [37] ). Finally, in normal samples, [39] found that perceived feedback accuracy fully mediated feedback choice, while[ [9] : Experiment 3] found that feedback consistent with self-views was regarded as especially informative.…”
Section: Some Questionable Evidence For Svtmentioning
confidence: 97%
“…[36][37][38] For example [16] found that, in a sample of cheerful and depressed people, ratings of feedback credibility and self-descriptiveness intercorrelated highly, and when amalgamated into a single index, predicted interest in interacting with evaluators (Experiment 1). In addition, both [17] and [18] found that, whereas cheerful people regarded flattering feedback as more accurate than critical feedback, depressed people regarded critical feedback as more accurate than positive feedback.…”
Section: Some Questionable Evidence For Svtmentioning
confidence: 99%